Recent Books on the Agricultural Situation - Davis, Joseph S. (Quarterly Journal of Economics, 1929)
Journal Article Recent Books on the Agricultural Situation Get access Joseph S. Davis Joseph S. Davis Food Research Institute, Stanford University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 43, Issue 3, May 1929, Pages 532–543, https://doi.org/10.2307/1885923 Published: 01 May 1929